Use of Information and Communication Technology at the Farmer Level in Kebumen Regency, Indonesia - Saridewi, Larasati Puspita; Annisa, Lolanda Hamim (Manunggal Halim Jaya, 2025)
Digital technology is crucial in advancing digital agriculture by enabling farmers to access valuable information such as planting schedules, pest and disease management, and market price trends. Despite its potential, the use of ICT by farmers remains limited due to inadequate internet access. In 2018, only about 25.7% of farmers in Indonesia had internet connectivity. Given this situation, it is essential to investigate the efficiency of ICT utilization among farmers, particularly in the Kebumen Regency. This research aims to understand farmers' perceptions of ICT usage and identify the diversity of ICT access at the farmer level. The study involved 90 rice farmers in Kebumen Regency. Access to ICT tools in this research refers to smartphones, computers, and laptops. Farmers' perceptions of ICT usage were assessed using a four-point Likert scale with the following options: strongly agree, agree, disagree, and strongly disagree. The development of the survey statements was guided by the Technology Acceptance Model (TAM) theory, which identifies two key factors influencing technology adoption: Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). The findings reveal that smartphones are the most widely used among the various ICT tools available to farmers. The study also indicates that farmers generally perceive the usefulness (PU) and ease of use (PEOU) of ICT tools. Based on these results, future agricultural extension strategies should prioritize the development of applications that are easily accessible via smartphones.